2005
DOI: 10.1021/jp040719j
|View full text |Cite
|
Sign up to set email alerts
|

Propargyl Radical:  Ab Initio Anharmonic Modes and the Polarized Infrared Absorption Spectra of Matrix-Isolated HCCCH2

Abstract: The propargyl radical has twelve fundamental vibrational modes, gamma(vib)(HCCCH2) = 5a1 [symbol: see text] 3b1 [symbol: see text] 4b2, and nine have been detected in a cryogenic matrix. Ab initio coupled-cluster anharmonic force field calculations were used to help guide some of the assignments. The experimental HC=:C-:CH2 matrix frequencies (cm(-1)) and polarizations are a1 modes--3308.5 +/- 0.5, 3028.3 +/- 0.6, 1935.4 +/- 0.4, 1440.4 +/- 0.5, 1061.6 +/- 0.8; b1 modes--686.6 +/- 0.4, 483.6 +/- 0.5; b2 modes-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
72
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(84 citation statements)
references
References 45 publications
12
72
0
Order By: Relevance
“…Recently, a number of works have demonstrated that ANO basis sets coupled to the CCSD(T) treatment of electronic correlation provide excellent results for level positions. 32,33,46,48,57,58 While excitations from the K shell molecular orbitals were not considered at the CCSD(T)/ANO2 level (i.e., frozen core), core correlations effects were tested for the Dunning's basis sets, by correlating all the electrons and using the core-valence aug-cc-pCVnZ (n = T or Q) functions. 55 In an explanatory run, the anharmonic force field of CH 2 F 2 was evaluated using either the frozen core CCSD(T)/aug-cc-pVTZ or the fully correlated CCSD(T)/aug-cc-pCVTZ levels.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, a number of works have demonstrated that ANO basis sets coupled to the CCSD(T) treatment of electronic correlation provide excellent results for level positions. 32,33,46,48,57,58 While excitations from the K shell molecular orbitals were not considered at the CCSD(T)/ANO2 level (i.e., frozen core), core correlations effects were tested for the Dunning's basis sets, by correlating all the electrons and using the core-valence aug-cc-pCVnZ (n = T or Q) functions. 55 In an explanatory run, the anharmonic force field of CH 2 F 2 was evaluated using either the frozen core CCSD(T)/aug-cc-pVTZ or the fully correlated CCSD(T)/aug-cc-pCVTZ levels.…”
Section: Methodsmentioning
confidence: 99%
“…6,7,16 For propargyl, quantum chemistry (CCSD(T)/ANO) predicts that 35% of the electron spin density resides on the terminal acetylenic carbon while the remaining 65% is on the methylenic carbon. 22 The resonance stabilization energy associated with this electron delocalization has been computed to be ≈11 kcal·mol −1 . 22 Because this stabilization energy is lost upon C−O bond formation, the C 3 H 3 −OO (propargyl peroxy) radical is less strongly bound than typical alkylperoxy radicals, 23 and unlike alkyl + O 2 , the propargyl + O 2 reaction is predicted to proceed over a small entrance channel barrier (≈1−4 kcal·mol −1 ).…”
Section: Introductionmentioning
confidence: 99%
“…22 The resonance stabilization energy associated with this electron delocalization has been computed to be ≈11 kcal·mol −1 . 22 Because this stabilization energy is lost upon C−O bond formation, the C 3 H 3 −OO (propargyl peroxy) radical is less strongly bound than typical alkylperoxy radicals, 23 and unlike alkyl + O 2 , the propargyl + O 2 reaction is predicted to proceed over a small entrance channel barrier (≈1−4 kcal·mol −1 ). 23 Hence, the propargyl radical is less reactive with O 2 and is therefore oxidized less effectively in comparison to nonresonantly stabilized radicals, leading to high concentrations in combustion environments.…”
Section: Introductionmentioning
confidence: 99%
“…Going to the ANO set that is the same size as cc-pVQZ (ANO2), the situation improves yet further [10]. Indeed, such calculations were instrumental in our assignment of the infrared spectrum of matrix-isolated cis-cis HOONO [11], and the propargyl radical [12].…”
Section: Introductionmentioning
confidence: 99%